Risk transfer: A mechanism to make the Macedonian agricultural sector more resilient to climate change - Nadica Jovanovska Boshkovska; Ana Sekulovska (University American College Skopje, 2020)
Agriculture is an important sector for employment, food supply and trade exchange in N. Macedonia. It's a climate sensitive sector that strongly rely on weather conditions. Therefore, the agriculture sector needs a risk management model that will cope in a most efficient way with the consequences of the climate changes. The common knowledge is that insurance is the most efficient and economical way to protect against financial losses in agriculture caused by climate changes. However, in Macedonia, despite the existence of a 60% premium subsidy, on average only 2% of registered farmers are insured. As a result, 98% of farmers are vulnerable to weather extremes, which are becoming more frequent due to climate change. This puts the government in the position of insurer of last resort, which in long run is fiscally unsustainable. To address the challenges with the persistent low insurance penetration, adverse risk selection, and excessive government fiscal exposure to climate change in agriculture the paper identifies the needs of a risk sharing system i.e. agriculture insurance pool. The pool will deliver a universal financial protection for every farmer, fast and fair claims settlement and a better adaptation of the agricultural sector to the climate changes. In parallel, will release the budget burden and allow its better allocation. This paper provides insight on development of a risk management systematic solution against natural disasters in agriculture. It applies secondary market data comparing the current state with the potential of the agriculture pool. The findings show that implementing an agriculture insurance pool is the most sustainable long-term solution which will reduce the impact of climate changes on the government budget and allow swift assistance to most vulnerable groups.
Keywords: 330; insurance; risk management; risk transfer; agriculture pool; climate change